Vitamin D & endothelial function - Alyami, A.; Soares, Mario; Sherriff, Jill; Mamo, John (Indian Council of Medical Research, 2014)
There is increasing interest in the extra-skeletal roles of vitamin D for health and well-being. Poor vitamin D status has been associated with obesity, cardiovascular disease, type 2 diabetes and mental health. Endothelial dysfunction may underscore insulin resistance and hence predispose to both cardiovascular disease (CVD) and type 2 diabetes. The objective of this review was to gain an appreciation of the recent causative evidence linking vitamin D and endothelial function. The PubMed database was searched from 2009 to date. Key words used were vitamin D, supplementation, systemic inflammation, endothelium, endothelial dysfunction and humans. Selected articles were restricted to the English language and to randomized control trials (RCTs) of vitamin D supplementation with direct measures of endothelial function. Final inclusion was based on a quality rating ≥ 3, based on the Jadad score. Ten RCTs met these criteria and were summarized for their outcomes. Only two studies showed an improvement in flow mediated dilatation with vitamin D. Three other studies reported decreases in C-reactive protein, platelet activation inhibitor-1, tissue plasminogen activator or B type natriuretic peptide. Recent evidence from good quality RCTs did not support a beneficial effect of vitamin D on vascular reactivity. Future intervention studies may need to target a higher vitamin D status and longer duration to determine whether the vitamin has a regulatory role in endothelial function.